Management of Village Common Land for the Improvement of Village Own-Source Revenue in Purwodadi Village, Tepus Subdistrict, Gunungkidul Regency - Aisyah, Siti (Marcapada: Jurnal Kebijakan Pertanahan, 2024)
The Special Region of Yogyakarta is an area that has a Special Law governing land affairs. Village Common Land is distributed across various regions, making it crucial to understand its ownership and management system, particularly in Yogyakarta. This study aims to explore the duality of the status of Village Common Land and its management for increasing local revenue in the village. This research uses a descriptive qualitative method with a descriptive approach. The findings indicate the presence of dual ownership status of Village Common Land. The management system includes subjects and objects, licensing, protection of Village Common Land, management of Village Common Land used for public facilities, business premises, and educational institutions, along with a profit-sharing system. There is potential for contributions from the management of Village Common Land, which can be used for development. In conclusion, the management of Village Common Land for the improvement of Village Own-Source Revenue (PAD) is effective, and it is recommended that the government further optimize the management of Village Common Land, while the community should utilize Village Common Land in accordance with existing regulations.